Stokes flow over a contaminated fluid sphere embedded in a porous medium with slip condition - Meduri, P.K.; Devi, P.N.L. (Archives of Mechanics, 2024)
In this paper, Stokes flow past a contaminated fluid sphere embedded in a porous medium is considered using interfacial slip on the boundary. The stream functions and drag are computed analytically. Special cases are deduced for drag force and a satisfactory agreement is reached with available data in the literature. It was observed that in viscous fluid and couple stress fluid cases with an increase in the viscosity ratio, the slip parameter, the porous parameter there is an increase in the values of the drag coefficient for varying different parameters, respectively. Also noticed that coefficient of drag values for a uniform flow of the viscous fluid flow over a contaminated viscous fluid sphere in a porous medium with the slip condition are superior to those of a couple stress fluid (CSF) flow.